Analyzing the influence of regulatory capture on environmental efficiency within institutional frameworks - Feng Wang; Feng Wang; Farooq Muhammad Sabil; Farooq Muhammad Sabil; Nazia Feroze; Cheng Tongshun; Faisal Feroze (Frontiers in Environmental Science)
IntroductionRegulatory capture presents a significant obstacle to achieving environmental efficiency, which is essential for the sustainable development of China's economy. Many efforts to enhance environmental efficiency are fundamentally shaped by the institutional frameworks underpinning them. This study investigates the theoretical and empirical relationship between regulatory capture and environmental efficiency, emphasizing the mediating role of institutional factors such as government quality and legal frameworks.MethodsThis research adopts a dual approach, combining theoretical analysis with empirical evaluation. It utilizes provincial-level panel data from China and applies the Slack-Based Measure (SBM) model to assess environmental efficiency. Key institutional variables—including indicators of government quality and legal robustness—are incorporated to examine how they interact with and influence the effects of regulatory capture.ResultsFindings reveal that regulatory capture significantly hinders regional environmental efficiency. However, a strong institutional environment mitigates this negative impact. Specifically, the legal framework has a pronounced regulatory effect in regions with low government quality but high legal strength. Conversely, in areas with high government quality but weak legal systems, local governments play a more corrective role. Importantly, the adverse effects of regulatory capture diminish only when the institutional environment surpasses a certain threshold of effectiveness.DiscussionThe study underscores the critical need to address regulatory capture in the environmental governance process. Enhancing institutional quality—through improved government functioning and robust legal systems—can create a synergistic effect that improves regulatory effectiveness and environmental outcomes. Policymakers must recognize the distorting influence of regulatory capture and implement measures to strengthen institutional integrity, thereby fostering green and sustainable regional economic growth.